Pengaruh Waktu Kneading Terhadap Efektifitas Enkapsulasi Molekul Minyak Kemenyan pada β-Siklodekstrin (β-CD) - Fauzan Setiawan, Sri Benti Etika Hesty Parbuntari (Menara Ilmu, 2019)
Frankincense essential oil (Boswellia sp.) is useful as aromatherapy, cosmetic ingredients,antibacterial, anti-inflammatory and an anticancer, but essential oils are generallyunstable, susceptible to high temperatures, and easily oxidized. Encapsulation provides asolution to the problem. β-cyclodextrin is a good coating for the encapsulation of essentialoils. Research has been conducted to determine the complex stability of inclusions with avariety of kneading times. FT-IR analysis showed that there was a shift in the wavelengthbetween the parent molecule of β-cyclodextrin and the inclusion complex, namely theincrease of the hydroxyl group (-OH) in the inclusion complex so that the widening of theabsorbance band occurred. The melting point of the inclusion complex is almost close tothe pure melting point of β-cyclodextrin (>290ºC), the melting point of the inclusioncomplex with variations in kneading time 15 minutes, 30 minutes, and 45 minutesrespectively 290ºC, 286ºC, and 278ºC. This high melting point shows inclusion complexesthat are stable and not easily damaged.Keywords: encapsulation, frankincense, β-cyclodextrin, kneading, stability.